Edukasi Keuangan untuk Masyarakat yang Cerdas dan Sesuai Syariah di BPR Koto Baru, Kabupaten Dharmasraya - Deby Ramadani Putri (Yayasan Daarul Huda Kruengmane, 2026)
Financial literacy is an essential aspect of improving community welfare, particularly in response to the increasing diversity of financial products and services. Limited understanding of financial management and the principles of Islamic economics remains a challenge for many communities, including those in Koto Baru Village, Koto Baru District, Dharmasraya Regency. This condition may lead to poor financial decision-making, including ineffective income management, inappropriate use of financing facilities, and the selection of financial products that do not align with individual needs and Islamic values. This community service program aimed to enhance the financial literacy of the local community by providing education on smart, sound, and Sharia-compliant financial management. The program employed a participatory approach consisting of coordination with Bank Perkreditan Rakyat (BPR) Koto Baru, financial literacy counseling, household budgeting training, an introduction to Islamic economic principles, interactive discussions, financial management simulations, and evaluation through question-and-answer sessions and participant feedback. The target participants included residents living around BPR Koto Baru, comprising micro-entrepreneurs, homemakers, and members of the general public. The results indicated an improvement in participants' understanding of the importance of financial planning, simple cash flow recording, prudent debt management, emergency fund preparation, as well as the principles of the prohibition of riba (usury), transparent contractual agreements (akad), and profit-sharing mechanisms in Islamic economics. Furthermore, participants demonstrated strong enthusiasm for adopting more disciplined financial behaviors and making more responsible use of formal financial services. The program also strengthened the relationship between the community and the local financial institution as a partner in promoting financial inclusion and financial literacy.